Hesitation to vaccination for COVID-19 among the Brazilian adult population (Revista Contexto & Saúde, 2023)
Background: This study assessed the perceptions and attitudes of the Brazilian adult population about COVID-19 vaccines, seeking to identify which factors are associated with vaccine hesitancy and lack of trust in vaccines to support individual or group strategies for welcoming and guidance.Methods: This is a national survey using a self-report web instrument in a representative sample of the Brazilian adult population (N=1700). The survey included sociodemographic and quality of life (QoL) questions, general information on COVID-19, and a vaccine-specific questionnaire.Results: The vast majority of our sample expressed favorable opinions regarding COVID-19 vaccination, but there was also a minor fraction (2.2%) of respondents who are hesitant about COVID-19 vaccination. Most of them were males within the age range of 30 to 59 years and reported that their reasons for vaccine hesitation are mainly due to uncertainty about safety (57.9%) and efficacy (36.8%) of vaccines, followed by concern with their development, that is, the issue of timing and the adoption of a new development technology (28.9%). Further, while the impact of groups and peers on those who hesitate to vaccinate was not clear, their perception of a low risk of contracting the disease is evident.Conclusions: There is a need to develop targeted strategies to increase effective communication about the risks and benefits of COVID-19 vaccines. Uncertainty about the safety and efficacy of vaccines, the timing, and the adoption of new development techniques affect significantly the perceptions on the vaccine COVID-19 acceptance.
Keywords: COVID-19; SARS-CoV-2; Vaccines